PENERAPAN PRINSIP GOOD GOVERNANCE DALAM MEWUJUDKAN KOTA LAYAK ANAK DI KOTA PEKANBARU - Riska Kartini; Sujianto; Zulkarnaini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the application of good governance principles in realizing a Child-Friendly City in the City of Pekanbaru. The background of this research is based on the fact that there is still a gap between the achievement of the status of Child-Friendly City and the empirical conditions in the field, especially in the fulfillment of children's rights and protection. Therefore, good governance is needed as a foundation for the formulation and implementation of policies that are in the best interests of children. This research uses the theory of good governance according to Sedarmayanti (2004) which includes nine indicators, namely participation, rule of law, transparency, responsiveness, consensus orientation, justice, effectiveness and efficiency, accountability, and strategic vision.The research method used is a qualitative approach with the type of explanatory descriptive research. Data was collected through observation, interview, and documentation techniques at related agencies that play a role in the implementation of the Child-Friendly City program in Pekanbaru City. The data obtained is then analyzed in depth to describe the conditions for the implementation of the principles of good governance and identify supporting and inhibiting factors in its implementation.The results of the study show that the application of good governance principles in realizing a Child-Friendly City in Pekanbaru City in general has been running, but it is not fully optimal. Several indicators such as participation, justice, and effectiveness have shown good implementation through cross-sector coordination and programs that support the fulfillment of children's rights. However, there are still obstacles in the form of limited resources, suboptimal coordination between agencies, and uneven involvement of the community and children in the policy-making process. Thus, it can be concluded that the application of the principle of good governance in realizing a Child-Friendly City in Pekanbaru City requires strengthening the implementation aspect to be more effective, inclusive, and sustainable. This research is expected to contribute as an evaluation and recommendation material for local governments in improving the quality of governance oriented towards the fulfillment of children's rights and protection.